2011
DOI: 10.1007/s13197-011-0507-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of ω-3 fatty acid enriched low-fat chicken meat patties incorporated with selected levels of linseed flour/oil and canola flour/oil

Abstract: The aim of the present study was to compare the nutritional, processing and sensory characteristics of low-fat ω-3 enriched fatty acids chicken meat patties (CMP) prepared with the incorporation of 4% linseed flour (T 1 ), 2% canola flour (T 2 ), 3% linseed oil (T 3 ), and 4% canola oil (T 4 ) and to estimate their cost of production. The total fat and crude fiber content was increased (P<0.05) with the incorporation of linseed flour. The emulsion stability and cooking yield was greater (P<0.05) in T 4 among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…The standard nugget highly progressed to darkness than formulated sample, possibly because it contained higher fat content and no antioxidant ingredients like SP. This was in agreement with the study of Singh et al (2011) who showed that the decrease in L * in chicken nuggets with partial soybean oil replacement by linseed oil was attributable to less of a browning effect due to lower lipid oxidation. A significant decrease in redness value of both nuggets during storage was corresponded to protein denaturation/concentration, fat and water content, meat pigments and degree of oxidative reactions (Devatkal et al 2014).…”
Section: Colorsupporting
confidence: 93%
See 1 more Smart Citation
“…The standard nugget highly progressed to darkness than formulated sample, possibly because it contained higher fat content and no antioxidant ingredients like SP. This was in agreement with the study of Singh et al (2011) who showed that the decrease in L * in chicken nuggets with partial soybean oil replacement by linseed oil was attributable to less of a browning effect due to lower lipid oxidation. A significant decrease in redness value of both nuggets during storage was corresponded to protein denaturation/concentration, fat and water content, meat pigments and degree of oxidative reactions (Devatkal et al 2014).…”
Section: Colorsupporting
confidence: 93%
“…This is because most consumers would like to avoid the risks of fat-related diseases including cardiovascular disease, diabetes, obesity, hypertension and some cancers (Singh et al 2011). Reductions in harmful ingredients such as animal fat, salt and phosphates have been investigated for the manufacture of low-fat meat products (Mahmoud and Badr 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, addition of FF increased the fat content of product significantly due to higher fat content of FF (37.13%). Increase in the total fat of product on addition of flaxseed had also been reported by Singh et al (2011). Ash content of treatment products was almost similar to control.…”
Section: Resultssupporting
confidence: 77%
“…For many years, the main source of vegetable protein for shrimp feed was obtained from terrestrial plant, such as soybean meal (Cruz-Suarez et al, 2009;Suárez et al, 2009;Derby et al, 2016;Sharawy et al, 2016;Xie et al, 2016), lupin meal (Draganovic et al, 2014), garden pea Pisum sativum, concentrated rice protein (Oujifard et al, 2012;Chen et al, 2017), and canola meal Brassica sp. (Kou et al, 2015;Suárez et al, 2009;Singh et al, 2014). The ingredient selection is managed according to the nutrition and the digestibility (Cruz-Suarez et al, 2009;Samuelsen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%